2014
DOI: 10.1371/journal.pone.0110744
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma SK Hep-1 Cells Exhibit Characteristics of Oncogenic Mesenchymal Stem Cells with Highly Metastatic Capacity

Abstract: BackgroundSK Hep-1 cells (SK cells) derived from a patient with liver adenocarcinoma have been considered a human hepatoma cell line with mesenchymal origin characteristics, however, SK cells do not express liver genes and exhibit liver function, thus, we hypothesized whether mesenchymal cells might contribute to human liver primary cancers. Here, we characterized SK cells and its tumourigenicity.Methods and Principal FindingsWe found that classical mesenchymal stem cell (MSC) markers were presented on SK cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
0
43
0
2
Order By: Relevance
“…We believe this may be due to the fact that they do not possess any mRNA of hepatic-specific proteins (albumin and fibrinogen) or due to a difference in proliferation rate or cellular uptake mechanism of drugs/particles compared with the other cell lines [23]. Hence, in these highly resistant cells, we did not observe any IC 50 when incubated with all the drug molecules except doxorubicin.…”
Section: Resultsmentioning
confidence: 94%
“…We believe this may be due to the fact that they do not possess any mRNA of hepatic-specific proteins (albumin and fibrinogen) or due to a difference in proliferation rate or cellular uptake mechanism of drugs/particles compared with the other cell lines [23]. Hence, in these highly resistant cells, we did not observe any IC 50 when incubated with all the drug molecules except doxorubicin.…”
Section: Resultsmentioning
confidence: 94%
“…mRNAs of selected prometastatic genes, including cyclooxigenase 2 (COX2), DNA-binding protein inhibitor 1 (ID1), C-MET, matrix metallopeptidase (MMP)2, MMP9, CXCR4, CCR1, CCR6, and CCR7, were measured in SK-hep1 (SK) cells transfected with a control siRNA or with an NCoR-specific siRNA. These cells were derived from a patient with liver adenocarcinoma and recently have been shown to have an oncogenic mesenchymal stem cell phenotype (32). Most of these genes were significantly increased upon NCoR depletion in SK cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that CA suppressed cell proliferation and induced apoptosis in SK‐Hep‐1 cells. SK‐Hep‐1 cells possess aggressive migration and metastatic properties, which has been considered with mesenchymal origin characteristics . While the different tumor pathology between SK‐Hep‐1 cells (mesenchymal type) and hepatocytes (epithelial type), Eun et al demonstrates that SK‐Hep‐1 cells represent a transformation mechanism of mesenchymal stem cell into an enhanced self‐renewal cancer stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…SK‐Hep‐1 cells possess aggressive migration and metastatic properties, which has been considered with mesenchymal origin characteristics . While the different tumor pathology between SK‐Hep‐1 cells (mesenchymal type) and hepatocytes (epithelial type), Eun et al demonstrates that SK‐Hep‐1 cells represent a transformation mechanism of mesenchymal stem cell into an enhanced self‐renewal cancer stem cells . Thus, SK‐Hep‐1 cells are very critical cell lines applied in investigation, and the fact that the properties of the SK‐Hep‐1 cell line can be maintained in culture conditions and in vivo models makes it more suitable for HCC studies.…”
Section: Discussionmentioning
confidence: 99%